Comparison оf Digital Relief Models - S. A. Antonov; S. V. Peregudov (Наука. Инновации. Технологии, 2023)
Introduction. GIS technologies make it possible to analyze large amounts of spatial data, which include digital elevation models derived from remote sensing data. They are an important source of data for calculating and mapping various phenomena and processes that are closely interrelated with the relief, and cover vast areas. The article presents the results of the accuracy assessment of the three most popular global digital elevation models: ALOS World 3D, SRTM, and ASTER.Materials and research methods. The evaluation of digital elevation models was carried out on the territory of Budennovsky urban district of Stavropol Krai. Error analysis of morphometric indicators was performed based on the comparison of the studied digital elevation models and the data of the State Research and Development Center of Geoformation Systems and Technologies – GosGisCenter, which were presented in the form of topographic maps. The analysis of the results of the study was carried out based on mathematical and statistical methods. The total sample of compared points equals 5322.Research results and their discussion. Based on the obtained dataset of each of the digital terrain models, a comparative analysis of the samples was carried out. As a result, it was determined that the ASTER model showed the lowest accuracy. SRTM project data showed insignificant deviations. The digital terrain model based on ALOS W3D data has the highest accuracy.Conclusions. Despite its popularity and at first glance similarity of the data, a number of features of each of the digital terrain models were identified. The data obtained will simplify the selection of a digital terrain model, taking into account the requirements needed to perform various tasks, as well as improve the accuracy of the results obtained.